Modern management adding digital focus - Certo, Samuel C (New Jersey, USA Prentice hall, 2003)
The ninth edition of the modern management learning package, the text plus its ancillaries, continues a recognized and distinctive tradition in management education that has extended well over 20 years. This tradition emphasizes clear, concise, current, and through coverage based on an understanding of and a determination to enhance the student learning process. only instructional support materials that contribute to the design and conduct of the highest-quality principles of management course are included in the package. as in the past, revisions to this modern management learning package have been focused on single objective-improve student learning. All revisions reflect responsiveness to instructor and student learning. Strating with the text, the following sections explain each major component of this revision
Content in brief : Introduction to management -- Modern management challenges -- Planning -- Organizing -- Influencing -- Controlling -- Topics for speacial emphasis
A new tool for your principles of management course
Includes bibligraphical reference
12
Keywords: Controlling; Industrial management; Management; Planning; Social responsibility of business; Technological innovation